Напряженное состояние упругой полуплоскости при нестационарном нагружении - Кубенко, В.Д. (Прикладная механика, 2015)
Розвинуто методику обчислення напружено-деформівного стану пружної напівплощини при дії нестаціонарного навантаження, прикладеного до її границі. Сформульовано відповідну граничну задачу з початковими умовами. Застосовуються інтегральні перетворення Лапласа і Фур'є. Спільне обернення перетворень дозволило для деяких видів навантаження отримати точні аналітичні вирази для напруження і переміщення як функції відстані від границі і часу. A technique of evaluation of the stress-strain state of an elastic half-plane is developed when the applied to the half-plane boundary non-stationary load acts. The corresponding boundary problem with initial conditions is formulated. Laplace and Fourier integral transforms are utilized. The common inversion of transforms enables to obtain for some kinds of loads the exact analytical expressions for stresses and displacement as a function of time and distance from the boundary.